Social-demografic differences of educational migration perspectives among Kazakhstani high school students (The Journal of Psychology and Sociology, 2025)
The interrelation between migration and education represents a complex and dynamic process that has been examined in the academic literature from various research perspectives. In modern society educational migration has become a crucial factor in shaping individual opportunities, influencing access to educational resources and the quality of learning outcomes. The expansion of international programs and scholarships opens new prospects for Kazakhstani high school students planning to continue their studies at foreign universities. This article presents the results of a sociological study conducted among high school students from urban and regional schools to explore their educational plans regarding studying abroad. The collected data were analyzed using the SPSS software to identify socio-demographic patterns in the formation of educational trajectories after graduation. The findings demonstrate that academic criteria are the key determinant in choosing a foreign university. Information sources on studying abroad are primarily associated with digital channels (the Internet and social media); however, the family remains an influential factor especially for students from regional schools. The study also reveals gender- and location-based differences in the level of awareness of academic mobility programs. Interest in state-sponsored educational programs remains relatively high, though it varies significantly across gender and place of residence. Overall, the educational migration plans of Kazakhstani high school students are shaped by a combination of academic motivations and socio-demographic factors, reflecting the complex nature of decision-making in the field of educational migration.Research value: examining the educational migration plans of Kazakhstani high school students makes it possible to identify differences across various socio-demographic groups and to systematize the preconditions of non-returning educational migration at the macro, meso, and micro levels.Practical significance: the findings provide a basis for designing incentive strategies aimed at minimizing the risk of non-returning migration through a deeper understanding of how high school students’ migration plans are formed. The research methodology can be used in subsequent studies to identify the dynamics of changing migration plans and motives among young people.Keywords: educational perspectives, education, high school students, international programs, urban and regional schools.